Quantitative Detection of the Contrast of Electron Microscopic Images of Amorphous Nanomaterials with the Complex Chemical Composition - M.Y. Bobyk; V.P. Ivanytskiy; V.S. Kovtunenko; O.Y. Svatyuk (Журнал нано- та електронної фізики)
Physically strict detection of the contrast of electron microscopic images of amorphous nanomaterials has been proposed. The necessity of separation of the contribution to the contrast of different types of electron scattering by sample atoms, namely, resilient coherent, resilient non-coherent, and non- resilient, has been revealed. Simple analytical correlations for the determination of the contribution to the electron microscopic contrast of three different scattering types have been deduced.